Perianal Epidermodysplasia Verruciformis Associated With Human Papillomavirus 5 After a Renal Transplant. Issue 3 (July 2017) - Edwards, Libby; Reutter, Jason C.; Foster, Toby E.; Rady, Peter L.; Tyring, Stephen K.
Abstract : A 66-year-old woman developed perianal epidermodysplasia verruciformis–associated lesions after a renal transplant.